2018
DOI: 10.1080/2162402x.2018.1442168
|View full text |Cite
|
Sign up to set email alerts
|

Increase in PD-L1 expression after pre-operative radiotherapy for soft tissue sarcoma

Abstract: Soft tissue sarcomas (STS) have minimal expression of PD-L1, a biomarker for PD-1 therapy efficacy. Radiotherapy (RT) has been shown to increase PD-L1 expression pre-clinically. We examined the expression of PD-L1, pre- and post-RT, in 46 Stage II-III STS patients treated with pre-operative RT (50–50.4 Gy in 25–28 fractions) followed by resection. Five additional patients who did not receive RT were utilized as controls. PD-L1 expression on biopsy and resection samples was evaluated by immunochemistry using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 21 publications
1
60
0
Order By: Relevance
“…This would make comparative analyses reliable. Although radiotherapy has been shown to induce PD-L1 expression [33], our cases with documented post-radiotherapy (Table 1; n = 5) showed <10% PD-L1 expression. Finally, the size of the metastatic/recurrent cohort is limited and therefore, a larger number of paired samples is needed to further validate these findings.…”
Section: Fig 3 Matched Samples (A-d E-h and I-l Respectively) Primentioning
confidence: 57%
See 1 more Smart Citation
“…This would make comparative analyses reliable. Although radiotherapy has been shown to induce PD-L1 expression [33], our cases with documented post-radiotherapy (Table 1; n = 5) showed <10% PD-L1 expression. Finally, the size of the metastatic/recurrent cohort is limited and therefore, a larger number of paired samples is needed to further validate these findings.…”
Section: Fig 3 Matched Samples (A-d E-h and I-l Respectively) Primentioning
confidence: 57%
“…For instance, PD-L1 can be constitutive or inducible in response to IFN-γ released by effector T cells. Inducible PD-L1 can be affected by tumour location and prior therapy (Reviewed in [1]) including radiotherapy [33]. At the current time, there is not enough literature to address the dynamics of inducible PD-L1, as a result of therapy but if such changes occur, these may potentially provide therapeutic avenues to patients who may not initially be suitable for anti-PD-L1 therapy.…”
Section: Fig 3 Matched Samples (A-d E-h and I-l Respectively) Primentioning
confidence: 99%
“…Early studies have demonstrated that immunotherapy and radiation can safely be administered together and may induce responses, but questions remain regarding the optimal timing of systemic treatment with radiation, radiation dose, and tumour volume irradiated . Recent work in human sarcomas has suggested that radiation upregulates common targets of recently approved immune checkpoint inhibitors such as PD‐L1 . While immune checkpoint inhibitors have been approved for use in advanced disease settings or in conjunction with chemotherapy, none are approved for use with RT, and the mechanism for synergy remains incompletely understood .…”
Section: Immunotherapy Approaches For Canine Sarcomasmentioning
confidence: 99%
“…Cancer cells learn to evade the immune system by exploiting immune checkpoint pathways that prevent T lymphocytes from recognizing tumour-specific antigens. 124,125 There has been a recent change in clinical practice to incorporate immune checkpoint inhibitors into the management of a wide variety of advanced tumours, including melanoma, nonsmall cell lung cancer, lymphoma, head and neck tumours, gastrointestinal tumours, and genitourinary tumours. 60,126,127 Their use can also be extended to soft tissue sarcoma and osteosarcoma.…”
Section: Checkpoint Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation